Boron-based donor-spiro-acceptor compounds exhibiting thermally activated delayed fluorescence (TADF). Issue 31 (8th May 2018) - Stanoppi, Marco; Lorbach, Andreas
Abstract : We present highly luminescent borylated 2-phenylpyridines, which exhibit tunable delayed fluorescence due to their donor-spiro-acceptor architecture. Abstract : Four boron-based donor-spiro-acceptor compounds, composed of different donor moieties and borylated 2-phenylpyridines as the acceptor, were studied. Their intense photoluminescence in the solid state can be tuned by changing the donor and long emission lifetimes on the microsecond scale indicate thermally activated delayed fluorescence (TADF).